MARKETING STRATEGY THROUGH SOCIAL MEDIA IN INCREASING UMKM PRODUCT SALES VOLUME IN MASAMBA DISTRICTT - Nuraini, Nuraini; Anwar, Suhardi M; Pajarinto, Hadi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This research examines how social media marketing strategies influence the sales performance of MSMEs in the Masamba District. Methodology: Applying a quantitative approach, the study gathered data from 100 respondents selected through purposive sampling using questionnaires, and analyzed the results using multiple linear regression. Results: The overall marketing strategy did not have a significant influence on sales. In contrast, the utilization of Facebook and WhatsApp showed a positive and significant effect. Findings: When considered together, the marketing strategy along with Facebook and WhatsApp usage has a significant impact on sales volume. Focused utilization of these platforms is more effective than generalized marketing approaches. Originality: This research fills a void in the literature regarding the effectiveness of digital marketing among MSMEs in rural areas of Indonesia. Novelty: It highlights the distinct contributions of Facebook and WhatsApp as powerful tools for driving sales. Conclusion: While general strategies have limited impact, the strategic use of Facebook and WhatsApp can greatly enhance MSME performance. Type of Paper: Empirical research paper.